Degradasi Ekosistem dan Risiko Sosial Akibat Pertambangan Liar di Sekotong - Gilang Gilang; Liana Malik; Dian Warsito (Lembaga Publikasi Ilmiah Nusantara, 2026)
Illegal mining activities in the Sekotong area of West Lombok have triggered increasingly complex environmental and social problems. Mining practices carried out without proper management have led to ecosystem degradation, particularly through soil and water contamination caused by the use of hazardous chemicals such as mercury in the gold processing process. This condition has directly impacted the decline in environmental quality, disrupted public health, and increased the socio-economic vulnerability of the surrounding communities. This community service program aims to enhance public awareness and capacity in understanding the environmental and social risks caused by illegal mining activities, while also encouraging community-based mitigation efforts. The methods employed include socialization, participatory discussions, and assistance to communities and local stakeholders to identify the impacts of mining and formulate more sustainable alternative solutions. The results of the program indicate an increase in community understanding of the dangers of environmental pollution and its effects on health and the sustainability of natural resources. In addition, this activity has fostered a shared commitment to reduce environmentally harmful mining practices and to begin considering more sustainable livelihood alternatives. This program highlights the importance of collaboration between communities, local governments, and academic institutions in addressing the issue of illegal mining. Through a participatory and educational approach, this community service initiative is expected to serve as an initial step in strengthening ecological awareness and reducing the social and environmental risks associated with illegal mining activities in the Sekotong area.